1995
DOI: 10.1016/0029-7844(94)00409-7
|View full text |Cite
|
Sign up to set email alerts
|

Heparin versus normal saline as a peripheral line flush in maintenance of intermittent intravenous lines in obstetric patients

Abstract: During pregnancy, dilute heparin flush to maintain patency of intermittent IV site devices results in the following: a greater catheter patency rate at 48 and 72 hours after insertion of the catheter, a lower rate of catheter complications requiring therapy, and no alteration in PTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 6 publications
1
18
1
6
Order By: Relevance
“…11 14 When the results of two trials of 100 U/ml of intermittent heparin flush were pooled phlebitis was significantly decreased. 15 16 The test of homogeneity, however, was significant (P=0.0006) for the decreased risk of phlebitis, with one trial that used 100 U/ml every 6 hours16 showing a much larger but non-significant trend in the direction of heparin being beneficial than the trial that used 100 U/ml every 8 hours 15. When the data from seven trials of heparin at concentrations of 1 U/ml infusion flushed continuously through the catheter were pooled (see figure 2) there was a significant decrease in phlebitis with use of heparin.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…11 14 When the results of two trials of 100 U/ml of intermittent heparin flush were pooled phlebitis was significantly decreased. 15 16 The test of homogeneity, however, was significant (P=0.0006) for the decreased risk of phlebitis, with one trial that used 100 U/ml every 6 hours16 showing a much larger but non-significant trend in the direction of heparin being beneficial than the trial that used 100 U/ml every 8 hours 15. When the data from seven trials of heparin at concentrations of 1 U/ml infusion flushed continuously through the catheter were pooled (see figure 2) there was a significant decrease in phlebitis with use of heparin.…”
Section: Resultsmentioning
confidence: 96%
“…At doses of 100 U/ml flushed every 6 or 8 hours heparin was associated with a significantly lower loss of catheter patency when the results of two trials were pooled. 15 16 Heparinised infusion significantly decreased loss of patency in arterial catheters when the results of two trials were pooled. 22 23…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 32 studies were found to comply with the predefined inclusion criteria. The characteristics of the final 32 studies included in the present review are displayed in Table I, among which, there are 21 reported results for intermittent flushing (7)(8)(9)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and 11 evaluated heparin for continuous infusion (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In total, 10 studies reported multiple catheters per patient (15)(16)(17)23,25,27,(37)(38)(39)43), with the rest of the studies reported a single catheter per patient. The study populations included pediatric patients (14,15,21-24, 26-29,32,33,37-39,44), healthy volunteers and adults (7)(8)(9)16,17,20,30,31,(34)(35)(36)(40)(41)(42)(43), and the administered treatments in all studies primarily consisted of antibiotics and parenteral nutrition. Furthermore, the origin of countries reported included the USA (7,8,14,20,(26)(27)(28)30,32,33,35,43), the UK (39,40), Germany (38), France (36), the Netherlands (22), Australia (44), Italy (17), Canada (25), Ireland (34), India (15,31) and China (16)<...>…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…33,34 One trial of pregnant women demonstrated significantly increased efficacy and decreased complication rates with heparin-infused catheters compared with those flushed with 0.9% sodium chloride. 35 A subsequent study of pregnant women found no significant differences in the number of patent catheters or in complications with catheters flushed with either heparin or 0.9% sodium chloride, but the authors noted that their small sample size provided only 11% power to detect a significant difference in patency and even less power to detect a significant difference in complications. 36 Data from pregnant patients are conflicting; therefore, a recommendation cannot be made until more data are available.…”
Section: Introductionmentioning
confidence: 96%